Распространение внехромосомных кольцевых ДНК у Erwinia carotovora - Сергеева, Ж.Ю.; Товкач, Ф.И. (Видавничий дім "Академперіодика" НАН України, 2008)
The study of a plasmid composition of 54 Erwinia carotovora’s strains of different origins shows that 30% of these strains contain different extrachromosomal DNAs. These genetic elements belong to four discrete size classes. For the first time, the correlation of strains‘ plasmid maintenance and their belonging to a certain ecological niche is shown, and their sensibility to bacteriophages is studied. The restriction analysis of plasmids from the most widespread class detects a homology of E. carotovora’s extrachromosomal elements. Any correlation between strains‘ plasmid maintenance and the killer activity of carotovoricines of E. carotovora’s strains is not found.